2019
DOI: 10.1016/j.vaccine.2018.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine synergy with virus-like particle and immune complex platforms for delivery of human papillomavirus L2 antigen

Abstract: Diverse HPV subtypes are responsible for considerable disease burden worldwide, necessitating safe, cheap, and effective vaccines. The HPV minor capsid protein L2 is a promising candidate to create broadly protective HPV vaccines, though it is poorly immunogenic by itself. To create highly immunogenic and safe vaccine candidates targeting L2, we employed a plant-based recombinant protein expression system to produce two different vaccine candidates: L2 displayed on the surface of hepatitis B core (HBc) virus-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 59 publications
2
32
1
Order By: Relevance
“…By inserting the antigen into only one of two tandemly-linked HBc gene copies, it is possible to lessen the problem of destabilization, leading to an increased capacity of HBc VLPs to display antigens [36]. In addition, HBc VLPs can be efficiently produced in a number of expression systems, including plants [24,36,53,54]. In this study, we found that ZE3 displayed on either heterodimeric HBc or C-terminally fused to HBc monomer produced fully formed and highly immunogenic VLPs with nearly indistinguishable immunogenic properties (Figs.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…By inserting the antigen into only one of two tandemly-linked HBc gene copies, it is possible to lessen the problem of destabilization, leading to an increased capacity of HBc VLPs to display antigens [36]. In addition, HBc VLPs can be efficiently produced in a number of expression systems, including plants [24,36,53,54]. In this study, we found that ZE3 displayed on either heterodimeric HBc or C-terminally fused to HBc monomer produced fully formed and highly immunogenic VLPs with nearly indistinguishable immunogenic properties (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…RIC and VLP leaf samples were homogenized in ice-cold, 1:2 w/v extraction buffer at pH 8.0 (100 mM Tris-HCl, 50 mM NaCl, 10 mM EDTA, 0.1% Triton, 50 mM sodium ascorbate, and 2 mM PMSF). The VLP purification via sucrose gradient centrifugation and the RIC purification via protein G column chromatography purification protocol was conducted as described in [24]. For the N-terminal ZE3, the extraction buffer used was at pH 9.5 instead of pH 8.0.…”
Section: Protein Extraction and Purificationmentioning
confidence: 99%
See 3 more Smart Citations